2020
DOI: 10.3390/cancers12020367
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thromboprophylaxis in Ambulatory Cancer Patients: Where Do We Stand?

Abstract: Venous thromboembolism (VTE), comprising deep-vein thrombosis and pulmonary embolism, is a frequent complication in ambulatory cancer patients. Despite the high risk, routine thromboprophylaxis is not recommended because of the high number needed to treat and the risk of bleeding. Two recent trials demonstrated that the number needed to treat can be reduced by selecting cancer patients at high risk for VTE with prediction scores, leading the latest guidelines to suggest such an approach in clinical practice. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 86 publications
1
20
2
1
Order By: Relevance
“…The optimal way of identifying ambulatory cancer patients at high risk of VTE remains a matter of debate. 2,6,17,40,50,51 In this metaanalysis, we focused on the Khorana score, because it is the most widely studied and used risk-stratification tool. However, a substantial variation in VTE risk has been observed across different tumor types within the same Khorana score risk group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal way of identifying ambulatory cancer patients at high risk of VTE remains a matter of debate. 2,6,17,40,50,51 In this metaanalysis, we focused on the Khorana score, because it is the most widely studied and used risk-stratification tool. However, a substantial variation in VTE risk has been observed across different tumor types within the same Khorana score risk group.…”
Section: Discussionmentioning
confidence: 99%
“…3 VTE can lead to interruption or postponement of cancer treatment, decreased quality of life, 4 morbidity, and death. 5,6 The goal of primary thromboprophylaxis is to reduce the risk of first-time VTE and, consequently, its short-and long-term sequelae. Several randomized trials have evaluated the efficacy and safety of prophylactic-dose low molecular weight heparin (LMWH) for VTE prevention in ambulatory cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have tried to improve the Khorana score performance and proposed modifications by adding biomarkers, types of chemotherapy or performance status [52,66,67]. A recently published review aimed at the optimization of thromboprophylaxis in cancer patients has been considering all these aspects and suggested that prediction scores might be developed for specific cancer sites [68]. Pabinger et al [69] developed and validated a nomogram that included only tumor site risk category and D-dimer to assess the risk of VTE in chemotherapy-treated cancer patients [69].…”
Section: Vte Prophylaxismentioning
confidence: 99%
“…Proposed algorithm for a therapeutic strategy based on the evaluation of venous thromboembolism (VTE) risk in patients with advanced cancer on a simultaneous care program. The classical category of the Intermediate-risk patients defined by the Khorana score is no longer included, since the integration of detailed programs and evaluations allows a more specific discrimination among patients[68][69][70]73]. CHT: Chemotherapy; ECOG-PS: ECOG-Performance Status; TPX: Thromboprophylaxis.…”
mentioning
confidence: 99%